2003
DOI: 10.1007/s005350300067
|View full text |Cite
|
Sign up to set email alerts
|

Primary colorectal T-cell lymphoma

Abstract: We report here a case of primary colorectal T-cell lymphoma in a 49-year-old man. Eighteen years previously, he was diagnosed as having ulcerative colitis based on the findings of colonoscopy and a barium enema. Since then, he had been treated with salicylazosulfapyridine until the most recent episode. He was refered to our clinic with the chief complaint of abdominal pain and excretion of mucus, and for a workup of bowel lesions. Physical examination results were not remarkable, except for the presence of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…6,23 Previous reports have shown that intestinal lymphoma tends to arise from areas exposed to intense and long-standing infl ammation, such as the rectum. 28,29 In fact, an analysis of 21 cases of malignant lymphoma in UC patients conducted by Abulafi et al 30 revealed that 52.4% of the lymphomas originated in the rectum, compared to the 60% that develop in the cecum in isolated intestinal lymphoma cases. In the present case, the patient had a 6-year history of repeated hospital admis- sion for UC, and the lymphoma developed in the rectum, which had undergone severe infl ammation and displayed refractoriness.…”
Section: Discussionmentioning
confidence: 97%
“…6,23 Previous reports have shown that intestinal lymphoma tends to arise from areas exposed to intense and long-standing infl ammation, such as the rectum. 28,29 In fact, an analysis of 21 cases of malignant lymphoma in UC patients conducted by Abulafi et al 30 revealed that 52.4% of the lymphomas originated in the rectum, compared to the 60% that develop in the cecum in isolated intestinal lymphoma cases. In the present case, the patient had a 6-year history of repeated hospital admis- sion for UC, and the lymphoma developed in the rectum, which had undergone severe infl ammation and displayed refractoriness.…”
Section: Discussionmentioning
confidence: 97%
“…This differentiation is made by using cluster of differentiation antibodies (CD): CD3, CD4, CD7 and CD8 are determined in T cell lymphomas; CD10, CD19 and CD20 are determined in B cell lymphomas 11. In our patient, no staining was observed with CD3, whereas staining was observed with CD20.…”
Section: Discussionmentioning
confidence: 68%
“…The reported average survival rate is 24 months 2. There are different results for the impact of adjuvant chemotherapy and radiotherapy on survival 2 11 13. Although it is accepted that adjuvant treatment is necessary, there is still no consensus because of the small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…10 T-cell lymphoma and Hodgkin's lymphoma affecting the colon have been described but are rare. 11 Lymphomas are generally staged according to the number and sites of nodal and extranodal involvement, and multiple staging schemes have been described. The Ann Arbor staging system modified by Musshoff is widely used in clinical practice today 12 (see Table 2).…”
Section: Histologic Subtypes and Stagingmentioning
confidence: 99%